Natural Fractures in Low-Permeability Sandstone Reservoirs in the LD-A HPHT Gas Field, Yinggehai Basin: Implications for Hydrocarbon Exploration and Development - Li, Hui; Fan, Caiwei; Jiang, Zhenxue; Li, Jun; Li, Chao; Xu, Xuhui; Li, Fang; Hu, Gaowei (Frontiers in Earth Science, 2022)
Research on the characteristics and distribution of natural fractures is of great significance for gas accumulation analysis and guiding the exploration and development of low-permeability sandstone gas reservoirs. In this study, fracture identification and characterization were first carried out based on core and imaging logging. Then, comprehensive fracture development indicators were constructed to predict the distribution of fractures in single wells by conventional logging. The main factors that affect the development of natural fractures and the implications of fractures on hydrocarbon exploration and development were discussed. The result shows that natural fractures were mainly low-angle tectonic fractures in sandstone reservoirs. Most of these fractures were found to be unfilled, yet the distribution of the fractures in the thin sections belongs to the discrete fracture structure, indicating that the connectivity of the fracture system is poor. The development of natural fractures is mainly influenced by rock strength, petrographic composition and petrology, and fractures were more developed in sandstones with a higher content of brittle minerals. The fracture density was mainly distributed below 0.05 m/m and up to 0.1 m/m. In the present in situ stress state, all the natural fractures in the LD-A gas field are invalid fractures. The critical pressure increment of the natural fracture was approximately 16.5-25.4 MP/km, when the pore pressure exceeds this valus, the fractures changed to effective fractures. The research results provide new geological knowledge and guidance for the exploration and development of LD-A gas fields and other similar low permeability tight sandstone reservoirs.